Very-heavy sled training for improving horizontal-force output in soccer players - Morin, J.-B.; Petrakos, G.; Jiménez-Reyes, P.; Brown, S. R.; Samozino, P.; Cross, M. R. (International Journal of Sports Physiology and Performance, 2017)
Background: Sprint running acceleration is a key feature of physical performance in team sports, and recent literature shows that the ability to generate large magnitudes of horizontal ground-reaction force and mechanical effectiveness of force application are paramount. The authors tested the hypothesis that very-heavy loaded sled sprint training would induce an improvement in horizontal-force production, via an increased effectiveness of application.